PENGARUH KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN ASING, UKURAN DEWAN KOMISARIS, PROFILE PERUSAHAAN TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar - Aditya Aji Viantoni (AKT 16 UMY 028, 2016)
The objective of this study aims to analyze the effect of institutional ownership, foreign ownership, board size, the company partially and simultaneously on the disclosure of social responsibility in manufacturing companies in Indonesia Stock Exchange (IDX) 2013 until 2014 period. The samples used in this research was purposive sampling method. The population in this study were all manufacturing companies that have been listed in the Indonesia Stock Exchange 2013-2014 period. From a population of 149 manufacturing companies acquired 25 manufacturing company in the sample with a 2-year observation period (2013-2014). Data were analyzed using multiple linear regression analysis. Based on the results of data analysis result that institutional ownership has a significant and negative effect on CSR, so the first hypothesis is rejected. Foreign ownership have significant and negative effect towards CSR, so that the second hypothesis is rejected. Board size and significant positive effect on CSR, so that the third hypothesis is accepted. Company profile and have no significant negative effect on CSR , so the fourth hypothesis is rejected. The suitability of the model test results show that simultaneous institutional ownership, foreign ownership, board size, companies profile are effect on the company's social responsibility disclosure.